The Role Of Parole Officer For Clients In Probation Office In A Systematic Literature Review (Slr) - Jannata, Yasmin Azzhara; Widodo, Eko Rizqi Purwo (UNIVERSITAS PAKUAN, 2020)
This study aims to classify topics and concepts related to the research on the role of Community Counselors on Clients in Correctional Centers. Through descriptive analysis using Vosviewer and Nvivo-12 plus software, 286 Scopus indexed articles published by major publishers such as Emerald, MDPI, Sage, ScienceDirect, Springer, Taylor, Francis, and others were obtained. This research shows 50 concepts and is categorized into 11 groups. The dominant themes in the articles are Probation, Prison Officers, Parole Officer, Social Work, Probation Officers, Community Correctional Practices, Parole System, Core Correctional Practices, Community Correction, Rehabilitation, Probation Conditions. It is expected to help future researchers to develop this study. This method uses PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The role of community supervisors and correctional centers in each article taken from the Scopus database has almost the same results from each country. There is no comparison and further research needs to use a comparative analysis approach involving the Scopus and Web of Sciences (WoS) databases and use later years' articles.